2011
DOI: 10.1016/j.cbi.2010.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin as an inhibitor of snake venom secretory phospholipase A2

Abstract: As polyphenolic compounds isolated from plants extracts, flavonoids have been applied to various pharmaceutical uses in recent decades due to their anti-inflammatory, cancer preventive, and cardiovascular protective activities. In this study, we evaluated the effects of the flavonoid quercetin on Crotalus durissus terrificus secretory phospholipase A2 (sPLA2), an important protein involved in the release of arachidonic acid from phospholipid membranes. The protein was chemically modified by treatment with quer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 33 publications
(41 reference statements)
10
54
0
Order By: Relevance
“…In a study to evaluate the effects of the flavonoid, quercetin, on Crotalus durissus terrificus secretory phospholipase A2 (sPLA2), it was reported that the protein was chemically modified by treatment with quercetin, which resulted in modifications in the secondary structure as evidenced through circular dichroism (Kim et al, 2004). In addition, quercetin was able to inhibit the enzymatic activity and some pharmacological activities of sPLA2, including its antibacterial activity, its ability to induce platelet aggregation, and its myotoxicity by approximately 40% (Cotrim et al, 2011). Cochinchina momordica seed extract (SKMS10) was also shown to exhibit anti-inflammatory activities by down-regulating cPLA2 among other molecular mechanisms of action (Kang et al, 2009).…”
Section: Inhibition Of Phospholipase A2mentioning
confidence: 99%
“…In a study to evaluate the effects of the flavonoid, quercetin, on Crotalus durissus terrificus secretory phospholipase A2 (sPLA2), it was reported that the protein was chemically modified by treatment with quercetin, which resulted in modifications in the secondary structure as evidenced through circular dichroism (Kim et al, 2004). In addition, quercetin was able to inhibit the enzymatic activity and some pharmacological activities of sPLA2, including its antibacterial activity, its ability to induce platelet aggregation, and its myotoxicity by approximately 40% (Cotrim et al, 2011). Cochinchina momordica seed extract (SKMS10) was also shown to exhibit anti-inflammatory activities by down-regulating cPLA2 among other molecular mechanisms of action (Kang et al, 2009).…”
Section: Inhibition Of Phospholipase A2mentioning
confidence: 99%
“…Herein, sPLA2 and specific substrate 4-nitro-3-octanoyloxy-benzoic acid (4NOB3A) were used to screening samples with inhibitory properties (Cotrim, De Oliveira, Diz Filho et al, 2010). Briefly, crude extract is tested and if it inhibited the substrate cleavage by the enzyme, this extract is subjected to different extractions with increasing polarity solvents.…”
Section: Natural Compounds (Bioassay-guided Fractioning Of Secondary mentioning
confidence: 99%
“…Recently, such method has been used for the evaluation of the sPLA2 treatment with different NC, mainly flavonoids. (Cotrim, De Oliveira, Diz Filho et al, 2010;De Oliveira et al, 2009;Iglesias, Aparicio, Rodrigues-Simioni et al, 2005;Santos et al, 2011;Toyama, Diz Filho, Cavada et al, 2011). In these studies native and modified PLA2 with different flavonoids (naringin, quercetin and morin) were prepared in 10 mM sodium phosphate buffer pH 7.4.…”
Section: Treatment Of Spla2 With Ncmentioning
confidence: 99%
See 2 more Smart Citations